2011
DOI: 10.1002/app.33331
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chitosan beads as boron sorbents

Abstract: Parameters, such as pH, temperature, initial boron concentration, adsorbent dosage, and ionic strength, affecting boron adsorption onto chitosan beads were examined in this study. The following values were obtained as the optimum conditions in our studied ranges: pH 8.0, temperature ¼ 308 K, amount of chitosan beads ¼ 0.15 g, initial boron concentration ¼ 4 mg L À1, and ionic strength ¼ 0.1 M NaCl]. The adsorption kinetics were also examined in terms of three kinetic models: the pseudo-first-order, pseudo-seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The n value greater than 1 means an S-type isotherm and also corresponds to physical adsorption [46]. Similarly, Bursali et al [25] found that the Freundlich equation provided better conformity than the Langmuir equation: experimental data of boron adsorption on chitosan beads confirmed to the Freundlich equation on the basis of the formation of multilayer adsorption. Differently, the Langmuir equation gave the best fit of the experimental data for composite [chiNi(II)], made of chitosan and nickel(II) by Demey et al [33].…”
Section: Equilibrium Studiesmentioning
confidence: 66%
See 2 more Smart Citations
“…The n value greater than 1 means an S-type isotherm and also corresponds to physical adsorption [46]. Similarly, Bursali et al [25] found that the Freundlich equation provided better conformity than the Langmuir equation: experimental data of boron adsorption on chitosan beads confirmed to the Freundlich equation on the basis of the formation of multilayer adsorption. Differently, the Langmuir equation gave the best fit of the experimental data for composite [chiNi(II)], made of chitosan and nickel(II) by Demey et al [33].…”
Section: Equilibrium Studiesmentioning
confidence: 66%
“…Comparing of the maximum adsorption capacities of chitosan found in the literature, Co-CTS composites have a capacity of the same order of magnitude as other adsorbents, e.g. Bursali et al [25] calculated the adsorption capacity of boron on chitosan beads about 2.5 mg/g at 25 °C. Although composite [chiNi(II)], made of chitosan and nickel(II) hydroxide [33] and oxide/ hydroxide-based nanoparticles (NanoFe) [47] present better q, they have a great disadvantages.…”
Section: Equilibrium Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…[24][25][26][27] In addition, the reported adsorption capacities of various adsorbents are shown in Table 2. 18,26,[28][29][30][31] The amount of borate ion adsorbed on NA11 was greater than that of most other adsorbents. Therefore, NA11 would be useful for the adsorption of borate ions from aqueous solutions.…”
Section: Resultsmentioning
confidence: 89%
“…They can be obtained via electrospinning of chitosan/agarose solution to reduce the viscosity of the blend (Elsabee et al 2012). Chitosan can also be used for the absorption of anions, as boron species, that may interact with the NH 2+ groups of chitosan at basic pH (Bursali et al 2011;Wei et al 2011).…”
Section: Ion Binding Propertiesmentioning
confidence: 99%